Evaluation of compositional and engineering properties of offshore Venezuelan soils. Volume 3, Tuy Cariaco clays / by Rami Mishu, Charles C. Ladd, R. Torrence Martin, Daniel R. Spikula. - Mishu, Rami.; Ladd, Charles C. (Charles Cushing); Martin, Robert T.; Spikula, Daniel Robert.; INTEVEP, S.A.; Massachusetts Institute of Technology. Department of Civil Engineering. Constructed Facilities Division. (Tufts University. Tisch Library., 2019)
1 online resource : illustrations.; "Prepared for Instituto Technologico Venezolano del Petroleo."; "Geotechnical order no. 735."; "MIT/INTEVEP Offshore Research and Development Program"--Cover.; This report is made available as part of the Dr. Charles C. Ladd Collection. For more information, contact Dr. Lewis Edgers (ledgers@tufts.edu) or Dr. Jack Germaine (john.germaine@tufts.edu) in the Tufts University Civil and Environmental Engineering department.